2012
DOI: 10.1016/j.jcin.2012.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Outcomes of Post-Procedure Heart Blocks After Transcatheter Device Closure of Perimembranous Ventricular Septal Defect

Abstract: The outcome of PPHBs after transcatheter closure of pmVSD was satisfactory, as most patients recovered to normal conduction. Measurements of DLRD-SLTV, DAVD, and DDOV may be useful in predicting the incidence of PPHBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 22 publications
1
71
2
Order By: Relevance
“…This fact should be considered when counseling patients, their parents, and their personal physicians about symptoms that might develop and that need appropriate evaluation. Yang et al, 7 reporting on a series of 244 patients, deduced that the time of AV block emergence was an independent predictor of cAVB persistence. They showed that the earlier a cAVB developed after closure of the pmVSD, the more difficult was a recovery to normal conduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This fact should be considered when counseling patients, their parents, and their personal physicians about symptoms that might develop and that need appropriate evaluation. Yang et al, 7 reporting on a series of 244 patients, deduced that the time of AV block emergence was an independent predictor of cAVB persistence. They showed that the earlier a cAVB developed after closure of the pmVSD, the more difficult was a recovery to normal conduction.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Previous literature has described that cAVB can occur immediately or later after transcatheter occluder closure. [7][8][9] Since the exact mechanism of postoperative cAVB is not fully investigated, the occurrence of cAVB in patients treated with percutaneous interventions is unpredictable. Additionally, there is a lack of studies describing incidence of cAVB and predictors of pacemaker requirement following ventricular septal defect (VSD) closure.…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous device closure of perimembranous ventricular septal defect is increas ingly used as a successful alternative to surgical clo sure. 248 Arrhythmic complications, including BBB and e300 atrioventricular block, occur in 11% during the proce dure 248 and in 15% after the procedure, 249 with a 1% to 5.7% incidence of highgrade atrioventricular block. Time to the development of atrioventricular block ranged from intraprocedural to up to 7 days after the procedure, with most occurring by 3 days.…”
Section: Transcatheter Structural Interventionsmentioning
confidence: 99%
“…Time to the development of atrioventricular block ranged from intraprocedural to up to 7 days after the procedure, with most occurring by 3 days. Although atrioventricular block resolution often occurs with ste roids, certain characteristics of the ventricular septal defect and placement of the occluder 249 250 In a metaanalysis of 172 series comprising >13 000 patients, the incidence of atrioventricular block was 0.4%. 251 The overall risk of major periprocedural complications was 0% to 9.4% in the studies, with a pooled risk of 1.6%.…”
Section: Transcatheter Structural Interventionsmentioning
confidence: 99%
“…Over the last decade the success rate of transcatheter closure of pmVSD has increased significantly, while complications, such as aortic or tricuspid regurgitation and device motion, have decreased . Though the incidence of heart block after closure of pmVSD has remained the most concerning complication (approximately 4–5%), little consideration is given to the access‐related complications and access choices . We report, to the best of our knowledge, the first ever pmVSD closure performed through radial artery (RA) and basilic vein (BV) access (arm access).…”
Section: Introductionmentioning
confidence: 99%